Identification Misconception of Transport Substance on A Freshman Used Technique Certainty of Response Index (CRI) in the Study Biology UNP Education - Sari Emriyuni; Ardi Ardi; Yosi Laila Rahmi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Misconception is a concept that doesn’t suitable with the concept recognized by experts. Misconception whom occur in students’ selves prohibit the formed of relation with the new concepts and disrupt the realization of learning process. Misconception may occur in learning of biological concepts, for example in substance transport material. This material contains the concepts that underlie the understanding of students to know the further biological concepts. Understanding of substance transport material has been obtained since at school and it’s difficult to understand for abstract reasons so it has the possibility of misconception. Therefore, misconception needs to be known by teacher and followed up early. The aim of this research is to identify the misconception on the concepts of substance transport material which experienced by first year class students in study program of Biology Education of UNP. This research is descriptive research which conducted in study program of biology education. The population of this research are 179 students of class 2017. The sample is 25% of 179 members of population, which is 45 members. The taking of sampling used simple random sampling technique. The data used are primary data which taking by using multiple choice test accompanied by Certainty of Response Index (CRI) and analyzed through quantitative technical analysis by percentage.Based on the analysis of data, it can be known that the percentage of students with the highest misconception is on the concept of passive transport mechanism about 23,03%, then on the concept of active transport mechanism about 22,69%, on the concept of transport mechanism through ensocytosis and exocytosis about 21,11%, and the lowest is misconception on the concept of cell membrane structure about 15,55% Keywords: Misconception, substance transport, CRI